PREVENTION AND CONTROL OF CROSS INFECTION AT DENTAL LABORATORIES IN EAST JAVA PROVINCE OF INDONESIA - Inayati, Eny; Indiani, Sri Redjeki; Gofur, Nanda Rachmad Putra (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: infectious disease is one major important health issue. Dental technician is an occupation which has a risk to get infectious disease transmitted from saliva, blood or contaminated tools if universal precaution utensils did not use properly. Infection can be transferred through dental impression from surface contact, handpiece, burs, pumice, aerosol etc. Purpose: This study aim to find out desinfection implementation in dental laboratories located in East Java as a preventive and controlling action towards cross infection. Method: Data were obtained through questionnaire, the questionnaires were designed to get the information related to infection control from dental laboratories in East Java. The survey was conducted in 36 dental laboratories listed by Association of Dental Technician in East Java. Result: As much as 90% dental laboratories did not performed desinfection procedure to the dental impression received from dentist and never follow any desinfection training. AS much as 95% Dental laboratories believe universal precaution utensils can be infected but only 50% utilize universal precaution utensils. Eventhough if such infection occurs, the owner will be fully responsible. Conclusion: Prevention and management towards cross infection control in dental laboratories located in East Java still very low. Development and supervision towards dental laboratories operational by Indonesian government and professional association need to be improved. Education regarding infection control need to be performed through trainings and inserted infection control matters in dental technician study programme curriculum in Indonesia.